Academic Achievement and the Gender Composition of Preschool Staff - Mette Gørtz; Eva Rye Johansen; Marianne Simonsen (Institute of Labor Economics (IZA), 2018)
This paper uses register based data covering the entire population of Danish children enrolled in preschool in 2006-2007 to investigate whether the gender composition of preschool staff members affects the timing of school start and subsequent academic performance. To estimate effects of the share of male staff member in preschools, we exploit within-preschool differences in teacher gender composition across time. We find that the share of male staff improves child outcomes and that gains are larger for boys who did not have access to male teachers previously and among children with less readily access to male role models.
Keywords: J13; 330; teacher gender; preschool; redshirting; child development